Jalan Bakti dalam Upaya Inkulturasi Injil Kristus di tengah Masyarakat Tionghoa Kristen di Indonesia - Suryadi, Yohanes (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2015)
The ethics of ‘homage’ and its practice in the Chinese tradition is centered around the ethics of the family, but in Indonesia it might have been tainted by the ideological and political interests of the exploitating rulers. As a consequence, the various ethical-familial dimensions of a noble homage-ethics could have been manipulated as well and become a means for subtle ideological-religious oppresion. The political-ideological content of homage-ethics that has been deviated into ideological homage needs to be shown to the Chinese people in Indonesia, so that they may respond critically to the homage-tyranny that creates the slave mentality, which sometimes is tucked into the collective unconsciousness. The exploitating homage ideology in the Chinese culture might be replaced with Jesus Christ’s ‘homage theology’, which is liberating and transforming. The perfect homage act of Christ on the cross is theocentric, but it brings the grace of redemption with its total and transcendental implication, and it has the power to give birth to a ‘new human being’ free from interhuman exploitation, idolatry, immorality, and injustice.